Pathological changes of frozen shoulder in rat model and the therapeutic effect of PPAR‐γ agonist. Issue 4 (1st December 2020) - Chen, Jinfu; Zhu, Junjun; Zhu, Tianfei; Cui, Jiaming; Deng, Zhenhan; Chen, Kang; Chang, Chongfei; Geng, Yiyun; Chen, Fei; Ouyang, Kan; Xiong, Jianyi; Wang, Manyi; et al.
Abstract: Frozen shoulder is a common shoulder disorder characterized by a gradual increase of pain and a limited range of motion. However, its pathophysiologic mechanisms remain unclear and there is no consensus as to the most effective treatment. The purpose of the study was to investigate the effect of transforming growth factor‐β (TGF‐β) on fibrosis and inflammatory response of the shoulder joint of rat models and to explore the therapeutic effect of the peroxisome proliferator‐activated receptor‐γ (PPAR‐γ) agonist. In the study, the effect of PPAR‐γ agonist CDDO‐IM treatment on cell proliferation, migration, and extracellular matrix proteins synthesis (vimentin, α‐smooth muscle actin, collagen I, and collagen III) were tested by cell proliferation test, scratches test, real‐time quantitative polymerase chain reaction, and Western blot analysis. The frozen shoulder was also established on the rat model by injecting adenovirus‐TGF‐β1 into rats' shoulder capsule. Pathological changes of the frozen shoulder tissue of the experimental group and PPAR‐γ agonist treatment group were evaluated. The stiffness of joints of the three groups was tested. Inflammatory mediators' expression including cyclooxygenase‐1, interleukin‐1β, and tumor necrosis factor‐α of the shoulder was tested by enzyme‐linked immunosorbent assay, and the expression of extracellular matrix proteins was evaluated by hematoxylin and eosin staining and immunohistochemistry. The results showed that pathological changes of the frozen shoulder in the rat model include an abnormal proliferation of fibroblasts, infiltration of inflammatory cells, and disorder of fibrous structure, while rosiglitazone reduced the severity of the frozen shoulder in the treatment group. Clinically, PPAR‐γ agonists may be a promising target for the treatment of the frozen shoulder.